Developing collaborative learning approach-based essay writing materials in an Indonesian university - Tri Jampi Setiyorini Setiyorini; Hasti Robiasih; Silvester Goridus Sukur; Somchai Watcharapunyawong (Journal of English Language and Pedagogy, 2023)
This research aims to: (1) develop the collaborative learning approach-based essay writing materials and (2) reveal the effectiveness of the developed collaborative learning approach-based essay writing materials in improving students’ English writing skills/competence. This research was Research and Development (R & D). The research instruments were close-ended questionnaires and tests. The subjects of the study were 20 third-semester students of the English education department students at Universitas Muhammadiyah Purworejo. The researcher developed the collaborative learning approach-based essay writing materials based on the needs analysis results. The researcher explained the needs analysis results, developed the course grid as the guidelines to develop the essay writing materials, made the first draft, asked some expert judgments to evaluate the developed essay writing materials, and revised the developed essay writing materials based on expert judgments’ results. The researcher improved the layout appearance to enhance the quality of the developed essay writing materials. Then, the researcher assessed the effectiveness of the developed essay writing materials using paired sample t-test. The results showed that the significance value is 0.00 (0.00 < 0.05). It means that H0 is rejected and Ha is accepted. Thus, it can be concluded that the developed collaborative learning approach-based essay writing materials is effective in improving students’ writing skills.